Sustainability Challenge Traditional Market in the Face of Digital market in East Java - Sarie, Rena Febrita; Iswoyo, Andi; Aristyanto, Erwan (Wiga : Jurnal Penelitian Ilmu Ekonomi, 2025)
The purpose of this study is to formulate a strategy model for Sustainability Challenge Traditional Market in the Face of Digital Market in East Java. The problem of the existence of digital markets due to the development of internet technology has changed consumer shopping behavior from shopping offline or traditionally to shopping online. As a result, many traditional markets that sell their products offline are unable to compete and close their businesses. The problems are first, How dynamics of change shopping behavior in East Java. Second, How does digital market influence the traditional market in East Java. Third, What are the sustainability strategies traditional market in the face of digital market in East Java. The result of the study that there are five strategies for traditional market in the face of digital market. There are Service Excellent, Morality Value, Customer Database, Adaptation, Digital Literacy. This research uses qualitative approach, by interviewed key informant using snowball sampling technique. This informants of study were 49 people, with the criteria 18 people traditional market ‘s customers, 18 people online shoppers and 12 people sellers in traditional market, and one person as staffing in the traditional market.